Education experiences of Fırat University Faculty of Medicine during the Covıd-19 pandemic process - Kaygusuz, Türkkan Öztürk; Kaygusuz, İrfan (Tıp Eğitimini Geliştirme Derneği [EN], 2021)
COVID-19 has spread rapidly all over the world and has been declared a global pandemic by the WHO. During this epidemic process, the education and training of our universities have been interrupted, as in the whole world. Medical faculties were the most affected by this situation due to the prevalence of applied education. In this process, our faculty has managed to complete the 2019-2020 academic year in the best way by working in coordination with all stakeholders of our university. In our faculty, all courses were held online asynchronously, and clinical practice applications were completed face-to-face in the summer term.Interns continued their education in clinics. All exams were again conducted online on digital platforms.The pandemic process changed the classics of Medical Education, led us to search for new educational models, but showed the importance of practical applications in the clinical environment and the relationship of the master apprentice.

COVID-19, kısa zamanda tüm dünyaya hızla yayılmış ve Dünya Sağlık Örgütü tarafından küresel çapta bir pandemi olarak ilan edilmiştir. Bu salgın sürecinde tüm dünyada olduğu gibi üniversitelerimizin eğitim-öğretimi aksamış, uygulamalı eğitimin ağırlıklı olması nedeniyle bu durumdan en fazla tıp fakülteleri etkilenmiştir. Bu süreçte fakültemiz, üniversitemizin tüm paydaşlarıyla koordineli bir şekilde çalışarak 2019-2020 eğitim- öğretim bahar yarıyılını en iyi şekilde tamamlamayı başarmıştır. Fakültemizde tüm dersler asenkron olarak dijital platformlarda yapılmış, klinik pratik uygulamalar ise yaz döneminde temmuz ve ağustos aylarında yüz yüze yaptırılarak tamamlanmıştır. İntörnler kliniklerde eğitimlerine devam etmiştir. Bahar yarıyılındaki tüm sınavlar yine dijital platformlarda online olarak yapılmıştır. Pandemi süreci tıp eğitiminin klasiklerini değiştirmeye başlamış, bizleri yeni eğitim modelleri arayışına sevk etmiş ancak klinik ortamda pratik uygulamalar yapmanın ve usta çırak ilişkisinin önemini bir kez daha ortaya koymuştur.
COVID-19 Pandemi Sürecinde Fırat Üniversitesi Tıp Fakültesi Eğitim Deneyimleri
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi